Improved Splenic Function After Hematopoietic Stem Cell Transplant for Sickle Cell Disease. Issue 5 (12th January 2016) - Nickel, Robert Sheppard; Seashore, Elizabeth; Lane, Peter A.; Alazraki, Adina L; Horan, John T.; Bhatia, Monica; Haight, Ann E.
Abstract : Background: Splenic dysfunction is a significant complication of sickle cell disease (SCD). Hematopoietic stem cell transplant (HSCT) is a proven cure for SCD; however, its long‐term effect on splenic function is not well characterized. Procedure: We conducted a retrospective cohort study of pediatric patients who had HSCT for SCD at two transplant centers. 99m Tc liver–spleen (LS) scans were blindly reviewed and classified as demonstrating absent, decreased, or normal splenic uptake. Results: Considering all engrafted nonsplenectomized Hb SS and Sβ 0 ‐thalassemia patients with LS scans available, at a median of 2.0 years post‐HSCT (range 1.0–9.3 years) eight of 53 (15%) had normal, 40 of 53 (75%) decreased, and five of 53 (9%) absent splenic uptake. More patients had splenic uptake after HSCT: pre‐HSCT 14/38 (37%) versus post‐HSCT 34/38 (89%), P < 0.0001. Older age at HSCT was associated with worse splenic function post‐HSCT (median age at HSCT for absent uptake 16.6 years vs. present uptake 8.0 years, P = 0.030). Extensive chronic GVHD was also more common in patients with absent splenic uptake compared to patients with present uptake (absent 40% vs. present 6%, P = 0.064). Conclusions: HSCT significantly improves splenic function for most pediatric patients with SCD, but older patient age at time of HSCT and extensive chronic GVHD appear to be risk factors for poor post‐HSCT splenic function.